Robots as addressable non-persons: an analysis of categorial work at the boundaries of the social world - Muhle, Florian (Frontiers in Sociology, 2024)
Prompted by the material turn in the social sciences and the development of novel interaction technologies, lively debates in social theory have arisen regarding the agency of non-human entities. While these debates primarily involve exchanging theoretical arguments against the background of different theoretical positions, ethnomethodological membership categorization analysis (MCA) provides an empirical approach to questions of non-human agency. The article discusses the debate on non-human agency, demonstrates how MCA can be used to investigate categorial work at the boundaries of the social, and presents the example of an encounter between two museum visitors and a humanoid robot to show how the robot is categorized in a specific way as an ‘addressable non-person.’ In this way, it becomes clear that social-theoretical debates and empirically oriented MCA can mutually inspire each other and how the ‘basic categorization apparatus’ addresses new alterities.